Development of digital art and culture book for improving students learning outcomes - Ahliana, Ahliana; Nurhikmah, Nurhikmah; Anwar, Citra Rosalyn (Univeritas Papua, 2025)
This study aims to determine whether the learning resources in the form of digital art and culture books are valid, practical, and effective in improving student learning outcomes. The ADDIE model was used to develop digital books. The study was conducted on grade VII students at a junior high school in Bone. The books that were developed were validated by experts and the media. Trials on 3 students and 9 students to see the practicality of digital books. Meanwhile, 26 students were involved in learning for effectiveness testing. The development results showed that digital books were valid (80.00%) based on material validators and very valid (88.23%) based on media experts. Individual responses from three students showed practical books, followed by findings in the responses of 9 students and 1 teacher (percentage range 88-95). The effectiveness test results showed that the average before digital books was 60 with a